Google Classroom Based Arabic Language Learning at Madrasah Tsanawiyah Negeri 5 Tulungagung - Ahmad Nurcholis; Syaikhu Ihsan Hidayatullah; Nur Qomari; Abu Hanifa (Mantiqu Tayr: Journal of Arabic Language, 2024)
The need for learning on digital applications or platforms is currently very high. Arabic language learning is entering an era of industrialization where access to learning already uses applications or digital platforms. The use of contemporary applications such as Google Classroom will change learning patterns from paper-based to paperless. This article aims to explain and analyze Arabic language learning based on Google Classroom media which has been carried out at Madrasah Tsanawiyah Negeri 5 Tulungagung. Employing a qualitative approach, this study analyzed descriptive data in the form of speech or writing and the observable behavior of the research subject. Data were obtained from interviews, observations, and documentation, where the authors conducted research by going directly to the field to find data at Madrasah Tsanawiyah Negeri 5 Tulungagung. The findings showed that learning Arabic using the online model via Google Classroom is very effective and efficient. Google Classroom becomes an alternative media to create changes in learning, it changes the learning environment which was originally traditional to an effective activity by utilizing facilities and attractive media to produce the maximum learning outcomes. This research is expected to provide a scientific contribution as a solution to the learning process in the digital era. The researcher advises future researchers that there is still a lot of online media that can be analyzed further.